Переваги та недоліки існуючих підходів до вартісної оцінки інтелектуальних технологій - Косенко, Олександра Петрівна; Ткачов, М. М. (НТУ "ХПІ", 2014)
Проведено детальний аналіз існуючих методичних підходів до вартісної оцінки об'єктів інтелектуальної власності. Визначено основні переваги та недоліки порівняльного, витратного та дохідного підходу. Обґрунтовано можливості використання комбінованого підходу до визначення вартісної оцінки об'єктів інтелектуальної власності. Розроблено рекомендації по практичному використанні проаналізованих методичних підходів для вартісної оцінки різних об'єктів інтелектуальної власності на промислових підприємствах.

The detailed analysis of existing methodological approaches to the valuation of intellectual property. The main comparative advantages and disadvantages, expenditure and income approach. Proved the possibility of using a combined approach to determining the valuation of intellectual property. Recommendations for practical use of methods analyzed for different valuation of intellectual property in the industry. It is proved that the further development of methodological basis of valuation should be connected, first, using interval estimation, which in our opinion is, firstly, more flexible in determining transfer prices in a changing competitive environment, secondly, able consider more factors influence the cost and price of intellectual property, third, providing more opportunities for effective negotiations between the developer of the technology and its potential consumer when making transfer and licensing agreements. Existing methodical installation cost and prices patents and other intellectual property involves some of the important characteristics of a patent search, patent image among consumers and inventors, the level of citing patent applications in other patents and scientific publications.
Advantages and disadvantages of existing approaches to the valuation of intelligent technologies
Keywords: об'єкти інтелектуальної власності; методичні підходи; промислові підприємства; intellectual property valuation; methodological approaches; advantages and disadvantages